The Entrepreneurial Start-Up Process: The Role Of Social Capital And The Social Economic Condition - Chuluunbaatar, Enkhbold; Ottavia, Ottavia; Luh, Ding Bang; Kung, Shiann Far (Asian Academy of Management (AAM), 2011)
Entrepreneurship is a complex phenomenon that involves not only economic activity but also social mechanisms. The intention to become an entrepreneur is a matter not only of one’s individual personality but also of one's interaction with the social environment. This study has three main objectives: predicting the existence of entrepreneurial behavioural intentions in different socio-economic conditions; examining how entrepreneurial behavioural intentions formulate entrepreneurial behaviour; and identifying how social capital influences this relationship. It also aims to reveal the differences between entrepreneurs in a relatively mature free market economy (Taiwan) and a newly emerging free market economy (Mongolia). The analysis shows that socio-economic conditions affect the formation of entrepreneurial intentions. There are different approaches to building social capital in a relatively mature market and its newly emerging counterpart. The tendency of having high trust and social ties was found in Taiwanese entrepreneurs, while monitoring is commonly found among Mongolian entrepreneurs.